ECONOMIC ANALYSIS OF A PRODUCTIVE UNIT OF FAMILY-BASED ORGANIC COFFEE - Menegueli, Hélio Orlando; Ferrari, Jéferson Luiz; Siqueira, Haloysio Mechelli de; Batista, Ringo Souza (Coffee Science - ISSN 1984-3909, 2019)
The objective of this study was to analyze the economic analysis of a family-based organic coffee production unit, called Rossmann Grange, located in the municipality of Santa Maria de Jetibá/ES, Brazil, certified organic since 2001 using the records of cost and production for the period from 2006 to 2016. The following indicators were evaluated: total operational cost; net operating income; profit and cost ratio. The results obtained were: total operating cost of R $ 476.14/bag; net operating income of R$ 3,022.66/ha; index operating cost benefit of 1.27; and profitability of the invested capital of 26.53%.